New exact solitary pattern solutions of the nonlinearly dispersive R(m, n) equations - İnç, Mustafa (Pergamon-Elsevier Science Ltd, 2006)
In this paper, we establish exact solutions for the R(m, n) equations by using a new sc-nc method. As a result, abundant new exact solitary pattern, solitary wave, periodic wave and singular solitary wave solutions of this equation are obtained with minimal calculations. The new solitary pattern solutions have infinite slopes or cusps, solitary wave and singular solitary wave solutions. (c) 2005 Elsevier Ltd. All rights reserved.
Keywords: Elliptic Function Solutions; Traveling-Wave Solutions; Abundant Families; Compact; Explicit